KONTRA INTELIJEN DALAM MENGHADAPI OPERASI RAHASIA (CLANDESTINE) ASING MELALUI PENYELUNDUPAN NARKOBA DI INDONESIA - Mohamad Djatmiko (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2025)
Indonesia is facing a critical drug crisis, not only as a consumer but also as a producer of narcotics. Drug abuse, once concentrated in major urban centers, has now permeated even the most remote regions, with an estimated 3.3 million users, or approximately 1.73% of the population. The country has become a primary target for large-scale drug smuggling, with around 80% of illicit substances entering through maritime routes, while the rest are trafficked via air transport and land borders. Beyond mere profit-driven criminal activity, strong indications suggest that drug trafficking is part of a broader covert operation by foreign entities aimed at weakening Indonesia’s national resilience. This operation systematically targets the younger generation, eroding moral integrity and mental strength, ultimately destabilizing the nation from within. While direct evidence of such clandestine foreign involvement remains elusive, numerous indicators point to its existence. However, the challenge lies in the highly secretive nature of these operations, making them difficult to identify and counter. Moreover, Indonesia has yet to fully recognize and address drug smuggling as a potential strategic maneuver orchestrated by external forces. To effectively combat this existential threat, Indonesia must go beyond conventional counter-narcotics efforts and adopt an intelligence-driven approach. A well-coordinated and highly classified counterintelligence strategy is essential to detect, disrupt, and neutralize these clandestine operations. This requires a structured and systematic intelligence framework that integrates advanced methodologies, tactical precision, and covert operational capabilities. By doing so, Indonesia can fortify its national security, safeguard its younger generation, and dismantle any covert attempts to undermine its sovereignty.